The Sexual Citizen - Naffine, Ngaire (Victoria University of Wellington Law Review, 2006)
This introduction to the Sexuality and Citizenship Special Issue considers the concept of the sexual citizen. It also examines and draws together the themes of the papers that formed part of the symposium held on 28 and 29 November 2005. Modern legal relations are typically understood and affirmed as relations at a physical distance, transacted between individuals (not members of a sex or sexual grouping), who relate to one another in a contractual manner, out of personal choice, on their own terms and usually for rational economic purposes. Sex and affection have never gone away from such relationships. The author argues that the enduring problem is that the law of sex and affection has not been modernised, and that we do not know how to think of sex and sexuality in a liberal egalitarian manner. It is argued that our legal model for thinking about the loving and physical side of life remains deeply orthodox and patriarchal. Homosexual people are accordingly excluded from a legitimate form of sexual citizenship, which in turn results in an exclusion from a full and rich sense of national identity and public rights.